Rituales relacionados con murallas en el ámbito celtibérico (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Through a contextual lecture of the archaeological record, this paper points out the existence in Celtiberia of symbolic and ritual conceptions tied to the physical delimitation of the town and the construction of the wall, not only understanding the rampant as an element of military functionality, but also as a prophylactic barrier against anything perceived as a threat by the Celtiberian world view.